Clitoral metastasis from uterine cervical cancer: A case report and review of the literature - Yukiko Hino; Yuki Yamada; Sachiko Miura; Fumi Okada; Tomoko Uchiyama; Seiji Mabuchi (Gynecologic Oncology Reports, 2020)
A 81-year-old woman vaginal bleeding and vulvar pain. Pretreatment work-up revealed a 4.5 cm cervical cancer extended to the lower-third of the vagina and an isolated clitoral metastasis. The patient was treated with a multimodal treatment consisting with radiotherapy followed by clitoridectomy. She recovered uneventfully following the multimodal treatment, and is currently free of disease. Clitoral metastasis is extremely rare, however, this condition should be considered in cervical cancer patients during the pretreatment work-up or follow-up period, especially when patients complain of clitoral pain or enlargement.